Differential effects of corporate social responsibility on downsizing: Evidence from the United States. (7th February 2022) - Pekovic, Sanja; Wagner, Marcus; Vogt, Sebastian
Abstract: Based on an integrated theoretical framework, we argue that socially responsible firms aspire to higher ethical and moral standards than other firms and foster higher intrinsic motivation to avoid downsizing. In line with this, we develop hypotheses proposing a negative association of Corporate Social Responsibility (CSR) with downsizing incidence and downsizing severity. Using a panel data on U.S. firms over an eight‐year period, we confirm these hypotheses and find that CSR has a negative association with downsizing, which increases with the severity of downsizing. We discuss the implications of the findings and how our work contributes to the body of academic work on downsizing with CSR as an important novel firm‐level determinant that links to corporate sustainability and stakeholder engagement.